Corporate Social Disclosures and Financial Performance of Selected Nigerian Banks: Implications For Corporate Leadership - Ilemona, Joseph Grace; Kingsley, Adeyemo; Adaeze, Nwobu Obiamaka (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
The study examines the effect of corporate social disclosures on the financial performance of selected banks in Nigeria. The study uses the ex post facto research design to realize its purpose. The study focuses on six years from 2015 to 2021 financial year. The sample size comprises ten listed banks in Nigeria. The results show that there is a negative relationship between social disclosures and the financial performance of banks in Nigeria. The findings show that the social performance of the banking sector needs improvement. The findings align with prior studies on the effect of social disclosures on the financial performance of banks. However, the results of the current study do not agree with some prior empirical studies. This inconclusive evidence provides a framework to guide corporate leadership in the way they conceptualize social performance and the business case arising from the same. The study recommends that banks improve their social performance and make their social disclosures more transparent and measurable to actualize the ability of stakeholders to rely on social performance information.